KINERJA PENYULUH PERTANIAN LAPANGAN DALAM MENGEMBANGKAN USAHATANI JAGUNG DI KABUPATEN BENGKAYANG - Fiki, Fiki; Kusrini, Novira; Oktoriana, Shenny (Jurnal Sains Pertanian Equator, 2020)
ABSTRACTThis study aims to determine the performance of agriculture extention officers instructors based on farmers' perceptions and determine the relationship of agriculture extention officers performance with the level of development of corn farming in bange village, Sanggau Ledo District, Bengkayang Regency. The sampling method uses proportional random sampling. Data analysis uses descriptive analysis and Spearman Rank correlation analysis. The results of this study indicate that The relationship between the performance of agriculture extention officers with the level of development of corn farming has a significant relationship and has a positive correlation direction. Level of agriculture extention officers performance in Bange Village is relatively high based on the dominance of respondents who give a high score of 63% of respondents. Based on Spearman Rank correlation analysis, agriculture extention officers performance shows that the higher the farmer's assessment of PPL performance, the higher the level of their farming. Keywords: Agricultuture Extention Officers Performance, Farmers' Perception, Corn Farming, Spearman Rank Correlation.ABSTRAKPenelitian ini bertujuan untuk mengetahui kinerja penyuluh pertanian lapangan (PPL) berdasarkan dari persepsi petani dan mengetahui hubungan kinerja PPL dengan tingkat perkembangan usahatani jagung di Desa bange Kecamatan Sanggau Ledo Kabupaten Bengkayang. Metode Pengambilan sampel menggunakan proportional random sampling. Analisis data menggunakan analisis deskriptif dan analisis korelasi Spearman Rank. Hasil penelitian ini menunjukan bahwa hubungan antara kinerja PPL dengan tingkat perkembangan usahatani jagung memiliki hubungan yang signifikan dan memiliki arah korelasi positif.tingkat kinerja PPL di Desa Bange tergolong tinggi berdasarkan dominasi responden yang memberikan nilai tinggi sebanyak 63% responden. Berdasarkan analisis korelasi Spearman Rank kinerja PPL menunjukan semakin tinggi penilaian petani terhadap kinerja PPL, maka semakin tinggi juga tingkat usahatani mereka.Kata Kunci: Kinerja PPL, Korelasi Spearman Rank, Persepsi Petani, Usahatani Jagung.